Volatile organic compound patterns predict fungal trophic mode and lifestyle - Yuan Guo (Nature Portfolio, 2021)
Guo et al. characterize the volatilomes of 43 fungal species using an automated cuvette system and mass spectrometry. Their results show that VOC patterns can predict trophic modes, symbiotic lifestyle, substrate-use and host-type of fungi.